Social engagement and depressive symptoms in Korean older adults: The potential moderating role of employment status - Ji-Eun Lee; Seonji Kim; Jeehye Lee; Yun-Chul Hong; Kyung-Shin Lee; Hye Sook Min (PLoS ONE, 2026)
Background Social engagement is known to alleviate depressive symptoms among older adults, and continued employment in later life may serve as a key mechanism for sustaining social engagement. However, the impact of employment on mental health can vary depending on job quality and socioeconomic conditions. This study aims to examine the association between social engagement, employment status, and depressive symptoms among older adults in South Korea. Methods This study utilized data from the Korea Community Health Survey conducted biennially from 2017 to 2023, excluding 2021. The analytic sample consisted of 199,205 adults aged 65 years and older. Depressive symptoms were assessed using the Patient Health Questionnaire-9. The effects of social engagement, categorized by informal and formal engagement, were analyzed in subgroups based on employment status. Associations were examined using multivariable logistic regression analysis. Results All types of social engagement were significantly associated with depressive symptoms, with the strongest associations observed for contact with friends and participation in leisure or recreational activities. Employment status served as effect modifier of these relationships, with employed older adults generally showing a lower likelihood of depressive symptoms compared to their unemployed counterparts. The negative association with employment was particularly pronounced in the domains of friend contact and all types of formal social engagement. Discussion Our findings highlight the importance of promoting formal social engagement as a potential intervention strategy for preventing depression among older adults and emphasize the need to consider appropriate forms of employment as part of this strategy.